EFEK GAYA KEPEMIMPINAN TRANSFORMASIONAL DAN KOMPENSASI LANGSUNG TERHADAP KINERJA KARYAWAN MELALUI DISIPLIN KERJA SEBAGAI VARIABEL INTERVENING DI PT COCA COLA EUROPACIFIC PARTNERS SERANG - Permata, Nuniek; Saputra, Saripudin; Diantoro, Eman; Alamsyah, Alamsyah (Bussman Journal : Indonesian Journal of Business and Management, 2024)
To ensure the company survives and succeeds, management must maintain and enhance existing resources, including employee performance, as improved performance contributes to the company's productivity. This study aims to investigate the direct effects of transformational leadership and direct compensation on employee performance and their impact on work discipline at PT Coca-Cola Europacific Partners. The method used is quantitative, with a population and sample size of 45 sales employees. The results indicate that transformational leadership and direct compensation have a significant impact on employee performance and work discipline, with t-statistics greater than 1.96. Additionally, transformational leadership positively influences performance through work discipline, while direct compensation does not show an indirect effect on employee performance through work discipline